Multiple Strukturen der Regulierung: Ursachen, Konflikte und Lösungen am Fall des Leichtathleten Baumann - Florian Becker; Dirk Lehmkuhl (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2003)
The case of the German world class athlete Dieter Baumann serves as an example for the exploration of concurring regulatory structures resulting from the existence of multiple regulatory systems. After an analysis of these systems we explore the causes of their existence on the national and the international level as well as in the realms of state(s) and society. In addition we aim to present theoretical attempts for their solution in a concrete case.
Keywords: 330